Extraction of Keratin from Human Hair with Production of Biofertilizer from Waste Liquid of Hair Extraction and its Efficient Application on Growth Yield of Abelmoschus esculentus L - Unnikrishnan, Gayathri; Ramasamy, Vijayaraghavan (Asian Journal of Biological and Life Sciences, 2020)
Keratin has been attracting interest due to its stability against enzymatic degradation thereby allowing more predictable degradation profile for tissue regeneration. While the efficacy of keratin has been demonstrated in different tissue models, there has been no systematic study to investigate and compare the different routes of keratin extraction from human hair. Here, we introduce a technique for mass keratin extraction from human hair. Keratin was extracted from human hair using 7 M urea, 6g SDS and 15 ml of 2- mercaptoethanol. It resulted in 73 % yield of about 6.8 g of keratin from 10 g of human hair waste and low crystallinity but the protein formed aggregates with highest hydrodynamic average size of around 5 μm. However, to study the fertilizing property of waste water generated from keratin extraction, they are applied onAbelmoschus esculenthusL. and recorded its biometric characteristics for 90 days. It is observed that nitrogen loss is the drawback for hair waste fertilizer, meanwhile in this study, we have observed minimal nitrogen loss of <15 % from this hair waste water application. These results provide new insight into the extraction of keratin from human hair with implications for its use as an organic fertilizer.
Keywords: FE-SEM; Fertilizer; Hair waste; Keratin; Okra